Native Vineyard Non-Saccharomyces Yeasts Used for Biological Control of Botrytis cinerea in Stored Table Grape - Antonio Domenico Marsico; Matteo Velenosi; Rocco Perniola; Carlo Bergamini; Scott Sinonin; Vanessa David-Vaizant; Flavia Angela Maria Maggiolini; Alexandre Hervè; Maria Francesca Cardone; Mario Ventura (Microorganisms, 2021)
Postharvest spoilage fungi, such as Botrytis cinerea, are considered the main cause of losses of fresh fruit quality and vegetables during storage, distribution, and consumption. The current control strategy is the use of SO2 generator pads whose application is now largely under observation. A high quantity of SO2 can be deleterious for fresh fruits and vegetables and it is not allowed in organic agriculture. For this reason, great attention has been recently focused on identifying Biological Control Agents (BCA) to implement biological approaches devoid of chemicals. In this direction, we carried out our study in isolating five different non-Saccharomyces yeast strains from local vineyards in the South of Italy as possible BCA. We performed both in vitro and in vivo assays in semi-commercial conditions on detached grape berries stored at 0 °C, simulating the temperature normally used during cold storage, and obtained relevant results. We isolated three M. pulcherrima strains and one L. thermotolerans strain able to largely antagonize the development of the B. cinerea, at both in vitro and in vivo conditions. In particular, we detected the ability of the three isolates of M. pulcherrima strains Ale4, N20/006, and Pr7 and the L. thermotolerans strain N10 to completely inhibit (100% in reduction) the mycelial growth of B. cinerea by producing fungistatic compounds. We found, using an extracellular lytic enzymes activity assay, that such activity could be related to lipid hydrolyzation, β-1,3-glucanase and pectinase activity, and pectinase and protease activity, depending on the yeasts used. Results from our in vitro assays allowed us to hypothesize for M. pulcherrima strains Ale4 and N20/006 a possible combination of both the production of soluble metabolites and volatile organic compounds to antagonize against B. cinerea growth. Moreover, in semi-commercial conditions, the M. pulcherrima strain N20/006 and L. thermotolerans strain N10 showed relevant antagonistic effect also at low concentrations (with a significantly reduction of ‘slip skin’ incidence of 86.4% and 72.7%, respectively), thus highlighting a peculiar property to use in commercial development for organic agriculture and the handling process.